2021
DOI: 10.3389/fpsyg.2021.717817
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Post-stroke Cognition Among Geriatric Patients: The Role of Demographics, Pre-stroke Cognition, and Trajectories of Depression

Abstract: Stroke is a prevalent disease among geriatric population, which tends to deteriorate cognitive ability and mental health. In such context, cognitive impairment and geriatric depression generate mutually deteriorating impacts on each other. Using the Health and Retirement Study, this study examined depression and cognition before, immediately after, and 2 years after the onset of stroke. Through latent growth mixture modeling, four different trajectories of depression were identified: resilience, recovery, emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
1
10
0
1
Order By: Relevance
“…Other variables used in our analysis include time-invariant covariates, such as age at baseline, sex, race / ethnicity and baseline level of education, and time-variant covariates, including participants' current marital status; participants' measure of depressive symptoms, obtained using the center for epidemiological studiesdepression (CES-D) score (higher scores indicating more depressive symptoms); and selfreported history of hypertension, diabetes, cancer, heart disease, and psychiatric conditions. These covariates have been shown to be associated with post stroke cognitive decline and have been typically controlled for in prior studies investigating association of stroke with cognitive decline [12,13,[21][22][23].…”
Section: Ethics Statementsmentioning
confidence: 99%
“…Other variables used in our analysis include time-invariant covariates, such as age at baseline, sex, race / ethnicity and baseline level of education, and time-variant covariates, including participants' current marital status; participants' measure of depressive symptoms, obtained using the center for epidemiological studiesdepression (CES-D) score (higher scores indicating more depressive symptoms); and selfreported history of hypertension, diabetes, cancer, heart disease, and psychiatric conditions. These covariates have been shown to be associated with post stroke cognitive decline and have been typically controlled for in prior studies investigating association of stroke with cognitive decline [12,13,[21][22][23].…”
Section: Ethics Statementsmentioning
confidence: 99%
“…The association between depression and cognitive difficulties in individuals with PSD is thought to reflect the effect of co-occurring brain damage (hippocampal damage leads to forgetfulness and emotion-regulation difficulties) or changes in environment (sadness with reduced opportunities leading to trouble with attention and forgetfulness) [ 30 ]. Recently, Kang [ 31 ] found that those with severe PSD were more forgetful. Indeed, mild levels of depression are not always associated with cognitive deficits, suggesting that the use of screeners to diagnose depression will be misleading when the diagnosis was mild sadness instead of clinical depression [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kang [ 31 ] found that those with severe PSD were more forgetful. Indeed, mild levels of depression are not always associated with cognitive deficits, suggesting that the use of screeners to diagnose depression will be misleading when the diagnosis was mild sadness instead of clinical depression [ 31 ]. It is interesting to note that in our study there were higher rates of both memory and executive impairment in PSD compared to stroke patients without depression when evaluated in between-group analyses, but when used side by side in the regression analysis, the odds of PSD were significantly associated with memory loss and not executive difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term hopelessness affects stroke patients' mental and cognitive health. This situation is exacerbated by cognitive deterioration and depression (Jadidi et al, 2022 ; Kang, 2021 ). Compared to the study by Ge et al, our results are different.…”
Section: Discussionmentioning
confidence: 99%